Heat‐Shock Proteins. Issue 11 (11th November 2022) - Hagymasi, Adam T.; Dempsey, Joseph P.; Srivastava, Pramod K.
Abstract: Heat‐shock proteins (HSPs), or stress proteins, are abundant and highly conserved, present in all organisms and in all cells. Selected HSPs, also known as chaperones, play crucial roles in folding and unfolding of proteins, assembly of multiprotein complexes, transport and sorting of proteins into correct subcellular compartments, cell‐cycle control and signaling, and protection of cells against stress and apoptosis. More recently, HSPs have been shown to be key players in immune responses: during antigen presentation as well as cross‐priming, they chaperone and transfer antigenic peptides to class I and class II molecules of the major histocompatibility complexes. In addition, extracellular HSPs can stimulate and cause maturation of professional antigen‐presenting cells of the immune system, such as macrophages and dendritic cells. They also chaperone several toll‐like receptors, which play a central role in innate immune responses. HSPs constitute a large family of proteins that are often classified based on their molecular weight as Hsp10, Hsp40, Hsp60, Hsp70, Hsp90, etc. This unit contains a table that lists common HSPs and summarizes their characteristics including (a) name, (b) subcellular localization, (c) known function, (d) chromosome assignment, (e) brief comments, and (f) references. © 2022 Wiley Periodicals LLC.